Effect of beta‐blocker therapy on early mortality after emergency colonic cancer surgery. Issue 4 (27th September 2018) - Ahl, R.; Matthiessen, P.; Fang, X.; Cao, Y.; Sjolin, G.; Lindgren, R.; Ljungqvist, O.; Mohseni, S.
Abstract : Background: Emergency colorectal cancer surgery is associated with significant mortality. Induced adrenergic hyperactivity is thought to be an important contributor. Downregulating the effects of circulating catecholamines may reduce the risk of adverse outcomes. This study assessed whether regular preoperative beta‐blockade reduced mortality after emergency colonic cancer surgery. Methods: This cohort study used the prospectively collected Swedish Colorectal Cancer Registry to recruit all adult patients requiring emergency colonic cancer surgery between 2011 and 2016. Patients were subdivided into those receiving regular beta‐blocker therapy before surgery and those who were not (control). Demographics and clinical outcomes were compared. Risk factors for 30‐day mortality were evaluated using Poisson regression analysis. Results: A total of 3187 patients were included, of whom 685 (21·5 per cent) used regular beta‐blocker therapy before surgery. The overall 30‐day mortality rate was significantly reduced in the beta‐blocker group compared with controls: 3·1 (95 per cent c.i. 1·9 to 4·7) versus 8·6 (7·6 to 9·8) per cent respectively ( P < 0·001). Beta‐blocker therapy was the only modifiable protective factor identified in multivariable analysis of 30‐day all‐cause mortality (incidence rate ratio 0·31, 95 per cent c.i. 0·20 to 0·47; P < 0·001) and was associated with a significant reduction in death of cardiovascular, respiratory, sepsis and multiple organ failure origin. Conclusion: Preoperative beta‐blocker therapy may be associated with a reduction in 30‐day mortality following emergency colonic cancer surgery. Abstract : Reduces mortality